Comparative evaluation of the sedative and physiological effects of xylazine, detomidine, and medetomidine in Barbari goats - Zahir Shah; Abd Ullah; Shabana Naz; Taif Shah; Abdul Aziz; Kasim Sakran Abass; Ibrahim A. Alhidary; Rifat Ullah Khan; Muhammad Israr (Journal of Applied Animal Research)
This study aimed to assess the sedative and physiological effects of three alpha2-agonists in Barbari goats. Eighteen healthy goats (20.3 ± 0.8 kg, 16 ± 2.2 months) were administered xylazine (100 μg/kg; XYL), detomidine (50 μg/kg; DET), or medetomidine (6 μg/kg; MED). Heart rate, respiratory rate, rectal temperature, serum glucose concentration, and sedation duration were recorded. Heart rate significantly decreased within 5 minutes, reaching its lowest at 50, 40, and 25 minutes in the XYL, DET, and MED groups, respectively. Respiratory rate declined within 5 minutes, with the greatest reduction observed at 20 minutes in XYL and DET groups and at 25 minutes in the MED group. Rectal temperature significantly dropped at 15 minutes in XYL and MED groups and at 45 minutes in DET. Serum glucose levels increased at 30 minutes post-administration. The onset of sedation were 29 ± 3.74, 55.66 ± 5.57, and 28.83 ± 5.98 s and the onset of optimal sedation were 5 ± 2.28, 12.16 ± 2.99, and 9.75 ± 2.75 minutes, and the total duration of sedation were 77.59 ± 4.38, 85.38 ± 2.76, and 72.64 ± 4.35 minutes in the XYL, DET, and MED groups, respectively. All three alpha2-agonists can be safely used for pain relief during physical examinations and minor surgical procedures in goats.